Nanopartículas de sílice obtenidas a partir del bagazo de caña para la desinfección de Escherichia coli y Pseudomona aeruginosa (2021)
In this work, the synthesis of silica nanoparticles (SiNPs) obtained from sugarcane bagasse (BC) residues was carried out. The resulting material was evaluated by different particle and material characterization methods. Scanning electron microscopy (SEM) revealed particles with a size smaller than 100 nm, heterogeneous distribution and spherical morphology. The SEM result confirmed the chemical nature of the nanomaterial and the Fourier transform infrared spectroscopy (FTIR) analysis data evidenced a Si - O - Si vibration peak, which validates the synthesis of silica by the method used. In addition, the functionalization of cetyl trimethyl ammonium bromide (CTAB) on its surface was achieved. The X-ray diffraction (XRD) results showed a characteristic peak of amorphous silica, and the measurement of the zeta potential of the nanoparticles indicated the negative electrostatic charge on their surface. Six different concentrations of the synthesized SiNPs (10000 mg/L, 5000 mg/L, 500 mg/L, 50 mg/L, 5 mg/L, 0.5 mg/L) were used to study the growth inhibitory effect of Escherichia coli and Pseudomonas aeruginosa, which produced a significant reduction of colony forming units in both strains. When a range of concentrations between 500 - 10000 mg/L of SiNPs was used, there was total inhibition of bacterial growth in both cases. Likewise, ranges of SiNPs concentrations where the minimum inhibitory concentration (MIC) can be found were also identified. The experiments were carried out under controlled conditions of temperature, agitation and time; identifying that at 75 minutes of incubation there was a greater inhibition of bacterial growth in the MIC determination assay, compared to the samples that were subjected to longer incubation times.